The Effectiveness of Personal-Social Guidance Services through Strengths based Advising for the Development of Social Adjustment in Adolescents - Setiana, Setiana (Academia Edu Cendekia Indonesia (AEDUCIA), 2022)
Personal-social guidance through strengths-based advising is an effort to synchronize education with guidance and counseling services. This study aims to produce a personalsocial guidance model through strength-based advising to develop social adjustment in adolescents. The research problem formulation is the effectiveness of the personal-social guidance model through strengths-based advising on adolescent social adjustment. This study uses a quantitative and qualitative approach (mixed method). The model used is explanatory sequential mixed methods. The research results show that the social adjustment profile is in a low category, averaging 52%. The personal-social guidance model through strength-based advising can be effective for developing social adjustment. The social adjustment aspect with the highest significance is the recognition aspect, with a significance of .235 compared to other aspects.